PATUMOD: a compartment model of vegetation dynamics in wooded pastures - Gillet, François; Besson, Olivier; Gobat, Jean-Michel (My University, 2002)
A system of wooded pasture can be described by seven biological state variables (trees, shrubs, underwood grasslands, fallows, eutrophic meadows, oligrotrophic lawns and cattle) linked by a network of dynamic interactions, which are controlled by altitude and human activities. PATUMOD is a spatially implicit compartment model designed to simulate vegetation dynamics in such silvopastoral ecosystems at community level and according to an equilibrium paradigm. Computer simulations show that the state variables generally end up on a steady-state (one-point attractor), independent on their initial values but strongly dependent on cattle load. At a given altitude, to each value of the stock density is corresponding a stable equilibrium characterised by a given relative cover of each vegetation component. If the initial values are very far of the attractor, a long succession of intermediate stages is required before leading to the steady-state. A remarkable exception to this rule can occur at low altitude, with a repellor between switching trajectories towards two attractors, corresponding to a threshold between scarcely and densely wooded pastures. PATUMOD can be applied to simulate different management scenarios, which include changing global stock density and cutting trees or shrubs. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: community dynamics; silvopastoral ecosystems; simulation scenarios; stability; steady-state; sustainability; phytocoenosis; vegetation; succession; PLANT COMMUNITY; SUCCESSION; SIMULATION; ECOLOGY; EVOLUTIONARY; DISTURBANCE; ECOSYSTEM; SYSTEMS